The association between environmental endocrine disruptors and the risk of attention deficit and hyperactivity disorder in children: a systematic review and meta-analysis - Xu, Yuzhu; Xu, Jie; Aris, Ahmad Zaharin; Peng, Chang; Pan, Kai; Wang, Chengxing; Zeng, Yingxi; Yu, Jie (Academic Press, 2025)
Objective: To provide a theoretical basis for investigating ADHD etiology in children, we aimed to investigate an association between environmental endocrine disruptors (EEDs) and attention deficit and hyperactivity disorder (ADHD) in children. Methods: Relevant studies on the relationship between EEDs and ADHD in children from January 2008 to December 2023 were collected. The fixed-effects model was used for studies with I2 < 50 %, whereas the random-effects model was used for studies with I2 > 50 % per the results of the literature heterogeneity test. A sensitivity analysis was performed to evaluate the stability of the combined results. Furthermore, Egger's and Begg's tests were used in combination with funnel plots to evaluate publication bias. Results: In total, 19 articles were included in the present meta-analysis. These results indicated that BPA and PAE exposure would increase the risk of ADHD. The results of the meta-analysis of sex subgroups showed that exposure to BPA, PAEs, PAHs increased the risk of ADHD in male children, whereas an inverse association was observed between exposure to PFAS and ADHD in female children. Conclusion: EEDs included in this study, such as BPA and PAEs, were associated with the increased risk of ADHD in children.